El viaje urbano en tranvía como práctica (re)creativa en evocaciones literarias de voces masculinas - Elisabet Prudant (Les Cahiers ALHIM)
Travel by public transportation hasn't been much studied from a historical perspective that considers its possibilities as a cultural practice, imposing the idea that it is just a repetitive exercise of functional displacement. This approach can be reassessed to the extent that the historical analysis in its crossroads with literature, in which allows us to identify other ways of giving meaning to the urban route from a gender identity perspective The article analyzes literary evocations of male voices about tram travel, the most significant means of public transportation in Santiago de Chile during the period between the end of the 19th century and the first decades of the 20th. The sources give us some deeper meanings on childhood and youth yearnings, accounting for the prerogatives of the bodies of men belonging to middle and upper strata in their experience of daily displacement as an instance of recreation and artistic creation. This urban movements through trams and public transportation are closely discussed under two dimensions regarding the use "for himself" of the masculine collective trip: the playful and the exploratory.